Learning Models Through Cybergogy in the Digital Era - Anas Rohman; Rusdarti Rusdarti; Kardoyo Kardoyo; Sungkowo Edy Mulyono (International Conference on Science, Education, and Technology, 2023)
this article aim study neighbour development of online learning models in the digital era. In study This discussed neighbour cybergogy as a learning model online research _ about the influencing factors child educate in online learning , namely cognitive , emotional and social factors . So that these three factors can made as attention main a educator in do online learning in order three factor can controlled , which thing This impact to achievements cognitive , emotional and social child educate in learn . Therefore , the cybergogy model education requires a problem - based strategy social , because of this strategy can integrated with harmonious with three factors cybergogy , so can form cognitive , emotional and sensitivity social child educate .